Foetal and neonatal outcomes in first‐trimester pregnant women exposed to abdominal or lumbar radiodiagnostic procedures without administration of radionucleotides. Issue 5 (14th May 2013) - Choi, J. S.; Han, J. Y.; Ahn, H. K.; Ryu, H. M.; Kim, M. Y.; Chung, J. H.; An, G. H.; Nava‐Ocampo, A. A.
Abstract Background/Aim Little is known about exposures to low radiation doses in the first trimester of pregnancy and deterministic adverse effects in the offspring, and risks are extrapolated from catastrophic events or from exposures to radiotherapy. The study aimed to assess the foetal and neonatal outcomes of pregnant women exposed to radiodiagnostic procedures with abdominal or lumbar irradiation. Methods In a prospective cohort design, we studied the foetal and neonatal outcomes in 115 singleton pregnant women who required abdominal or lumbar radiodiagnostic procedures without the administration of radionucleotides, and in 527 age‐matched (±2 years) control pregnant women. Results In the exposed group, lumbar spine radiography (33.9%), plain abdominal radiography (16.5%) and upper gastrointestinal tract radiography with abdominal irradiation (15.7%) were the most common radiodiagnostic procedures. Major congenital malformations were identified in two (1.9%) babies born in the exposed group and in two (0.4%) babies born in the control group (odds ratio = 4.7; 95% confidence interval 0.7–33.6; P = 0.15). The rest of the foetal and neonatal outcomes was similar in the two groups except by a marginally higher rate of admissions to the neonatal intensive care unit among babies born to exposed women (odds ratio = 2.9; 95% confidence interval 1.0–9.4; P = 0.06). Conclusion Our results indicate that X‐ray and computed tomography scan exposure involving abdominal irradiation without the administration of radionucleotides is not associated with adverse foetal and neonatal deterministic outcomes. Efforts are required to reduce the use of radiodiagnostic procedures for general check‐ups in childbearing age women.